Investigation of Circle Doubt (Obfuscation) and Circular Reasoning to the Evidence of the Principality of Existence - Muhammad Reza Ershadinia (آموزه‌‌های فلسفه اسلامي)
Islamic philosophy, with its foundations of ontology (ontological), has established the most basic foundations of rational theology. Uncertainty and gradation in these principles inflicts irreparable damage on theology in a special (more peculiar) sense and transforms it into another path with transformative consequences. Principality of existence has a prominent, visible and irreplaceable role among all the central principles of ontology. Transcendent Wisdom has established this principle by recognizing its effective role. Opponents of it have, as a result of some inconsistencies results with their presuppositions, such as the unity of existence, distorted and induced doubt in its proofs. The main doubt is the accusation of circle doubt and circular reasoning by a seemingly heterogeneous spectrum, including anti-philosophers and some separatists (gradationists) in a polemical method. In this opportunity, attention will be paid to four reasons that are in this doubt. These reasons are: the argument of the goodness of existence, the argument based on the difference between the effects of external existence and the mental existence, the argument based on the refusal (impossibility) of doubt in gradation the quiddity and the argument of intensified (intensifying) motion. By presenting the contents of these arguments, the content of the doubt will also be tested against them. The analysis shows that the skepticism is due to insufficient attention to the principles of these arguments.